ChemInform Abstract: SO3H‐Functionalized Mesoporous Silica Materials as Solid Acid Catalyst for Facile and Solvent‐Free Synthesis of 2H‐Indazolo[2, 1‐b]phthalazine‐1, 6, 11‐trione Derivatives. Issue 14 (March 2016) - Amiri, Ali Alinasab; Javanshir, Shahrzad; Dolatkhah, Zahra; Dekamin, Mohammad G.
Abstract: Title compounds (IV) are efficiently synthesized under mild and environmentally friendly conditions using an SO3 H‐functionalized mesoporous nano‐scaled silica material as catalyst.